The influence of corporate social responsibility on organizational performances: A research in AP Vojvodina - Grubor, Aleksandar; Berber, Nemanja; Aleksić, Marko; Bjekić, Radmila (Anali Ekonomskog fakulteta u Subotici, 2020)
The goal of the research was to explore and determine the relationships between CSR related to employees and business and environmental performances. The authors conducted field research on the territory of Autonomous Provence of Vojvodina, Republic of Serbia in the period from October 2019 until the end of March 2020 to collect the data from business organizations on their CSR activities and organizational outcomes. The research is conducted as a part of a one-year research project funded by the Provincial Secretariat for Higher Education and Scientific Research of Autonomous Province of Vojvodina for the 2019 year. To explore these relations, there has been performed PLS analysis in the statistical software Smart PLS 3.